STUDY REGARDING THE EFFICIENCY OF A PHYSIOTHERAPY PROGRAM IN PAIN REDUCTION, PHYSICAL FUNCTION AND QUALITY OF LIFE IMPROVEMENT IN PATIENTS WITH HIP OSTHEOARTHRITIS - Doriana Ioana CIOBANU; Carmen Ileana ȘERBESCU (Editura Universităţii din Oradea, 2016)
Hip osteoarthritis is mainly characterized by articular cartilage lesisons (distrophy, erosions), lack of articular surfaces shape and contour due to femoral head distruction.Aim. This paperwork aims to emphasize the efficiency of a comprehensive rehabilitation program in functional and quality of life improvement and pain reduction, in patients with hip osteoarthritis.Subjects. This study was conducted in Clinical Rehabilitation Hospital from Baile Felix, on a group of 10 patiants with hip arthrosis, aged between 50 and 80 years old, 50% man, 50% woman, average weight &2 kg, IMC 25.6, duration of affection average 17 years, 50% retired from activity, 50% workers.Metods. As assessment tools were used: goniometry, 0-5 scale for muscular force and Womac index for pain and quality of life assessment. The exercise program aimed to increase hip muscle tonus and the increasing of hip jount mobility and stability due to a better crossing of femorla head in the acetabular cavity.Results. After following rehabilitation program, we found the reduction of pain (11±8.18 baseline versus 9±8.18 final), the improvement of hip joint moiblity (4.60±3.28 pretest versus 3.7±3.27 posttest), of physical functioning (43.20±26.75 pretest versus 40.30±26.42 posttest) and of quality of life (59.8±38.12 pretest versus 53±37.70 posttest). Conclusions: A rehabilitation program followed 5 times/ week, for two weeks, can lead to the improvement of hip joint mobility, to an increased muscular force of pelvic girdle and to the impovement of quality of life in patients with hip osteoarthritis